Research on the underwater cutting mechanism of flux-cored arc cutting for aluminum alloy process - Yu, Rui; Li, Wenhang; Wang, Jiayou; Wu, Mingfang; Wang, Jianxin; Wu, Jing; Maksimov, Sergii Yuri (Frontiers in Materials, 2023)
With the fast-growing demand of aluminum alloys in ships and deep-sea pressure structures, an accurate and efficient underwater cutting operation for aluminum alloy is significant. However, its underwater arc cutting mechanism is still not clear enough, which limits its further application. The challenges lie in poor underwater visibility and complex underwater environment. In this study, process experiments, underwater sensor, and numerical simulations were conducted during cutting process to investigate the cutting mechanism of 5,052 aluminum. Firstly, the effect of parameters were investigated on cutting current, voltage, and water depth on the underwater kerf formation. In addition, three typical kerf formations, including “V” type, “II” type and “∧” type, were found; Secondly, visual sensing system was setup to monitor the cutting arc trajectory and the combustion process during the cutting process. Specially, the underwater burning phenomenon was observed. Finally, Finite Element Analysis was performed to further analyze the underwater arc cutting kerf formation of aluminum alloy. A semi-ellipsoidal composite heat source was applied to simulate the underwater arc, and the aluminum thermal reaction-generated heat was introduced. A dynamic method named “birth and death elements” was utilized to simulate the removal of molten metal. The temperature test results show that the simulation process is feasible. All results showed that different cutting parameters led to different cutting mode and affected the kerf forming. 5,052 aluminum alloy in the deep water environment (≥50 m) kerf significantly narrowed. The kerf cross-section produces an inward concavity and the kerf surface is as wide as the cutting wire. The aluminum kerf forming process is greatly impacted by the process parameters and self-propagating high-temperature synthesis reaction during aluminum alloy cutting. The periodicity of the cutting process was computed by the numerical simulation with the arc motion trajectory monitored by the high-speed camera. The numerical results of temperature distribution and kerf shape were consistent with the experimental data, which revealed the cutting mechanism.